The spleen-strengthening and liver-draining herbal formula treatment of non-alcoholic fatty liver disease by regulation of intestinal flora in clinical trial - Hui, Dengcheng; Liu, Lu; Azami, Nisma Lena Bahaji; Song, Jingru; Huang, Yanping; Xu, Wan; Wu, Chao; Xie, Dong; Jiang, Yulang; Bian, Yanqin; Sun, Mingyu (Frontiers in Endocrinology, 2023)
Objective:Spleen-strengthening and liver-draining formula (SLF) is a formula formed according to the theory of “One Qi Circulation” (Qing Dynasty, 1752) of Traditional Chinese Medicine (TCM), which has shown significant therapeutic effect in patients with NAFLD in a preliminary clinical observation. In this study, we aim to explore the mechanism of SLF against NAFLD, especially its effect on glucolipid metabolism, from the perspective of intestinal flora. Methods: A prospective, randomized, controlled clinical study was designed. The study participants were randomly and evenly divided into control group and treatment group (SLF group). Furthermore, the feces of the two groups were collected before and after treatment. The intestinal flora of each group and healthy control (HC) were detected utilizing 16S rRNA gene sequencing. Results: SLF group showed significant improvements in liver function, controlled attenuation parameter (CAP), and liver stiffness measurement (LSM), meanwhile, patients had significantly lower lipid and homeostasis model assessment of insulin resistance (HOMA-IR) with better security. Intestinal flora 16S rRNA gene sequencing results showed at the phylum level, Desulfobacterota levels were reduced. Firmicutes levels were significantly higher in patients with ALT or AST abnormalities, while Bacteroidetes was significantly lower. Clinical correlation analysis showed that Firmicutes positively correlated with gender, age, ALT, AST, LSM, and Fibroscan-AST (FAST) score, while the opposite was true for Bacteroidetes. At the genus level, the levels of Alistipes, Bilophila, Butyricimonas, Coprococcus, Lachnospiraceae_NK4A136 group Phascolarctobacterium, Ruminococcus, UCG-002, and UCG-003 were reduced, whereas abundance of Tyzzerella increased. At the genus level, Coprococcus (Lachnospiraceae family), Lachnospiraceae_NK4A136 group (Lachnospiraceae family), and Ruminococcus (Ruminococcaceae family) were significantly higher in the SLF group after treatment, and there was also a tendency for Bilophila (Desulfovibrionaceae family) to be back-regulated toward HC. Conclusions：SLF can improve liver function and glucolipid metabolism in patients with NAFLD and lower down liver fat content to some extent. SLF could be carried out by regulating the disturbance of intestinal flora, especially Coprococcus, Lachnospiraceae_NK4A136 group, and Ruminococcus genus.